Reimagining mobility-oriented landscapes a pedestrian simulation-aided approach to landscape planning in Guiguinto, Bulacan - Villegas, Mikaela Angela C.; Madonna P. Danao; Diomari G. Centeno (Quezon City College of Architecture, University of the Philippines Diliman, 2025)
Public transportation is considered the lifeline of cities for the way it efficiently facilitates the movement of thousands of commuters per day. Majority of the Filipino population favor the use of public transportation for its efficiency and affordability. However, infrastructure development continues to be car-centric, putting pedestrians and commuters as secondary users of transportation and their needs as mere afterthoughts. The objective of this study is to develop landscape design and planning guidelines that are focused on mobility and the needs and perception of pedestrians and commuters and is guided by transit-oriented development (TOD) frameworks. Furthermore, it aims to utilize simulation tools to validate the potential impact of development. This study was conducted through the assessment of the current state of public transportation, discussions and interviews on the perception of the stakeholders, and the development of transit-oriented development design and planning guidelines, aided by public transport simulation. Key findings from the data analysis revealed that (1) spatial quality of public transportation landscapes impact the behavior of commuters, (2) lack of pedestrian-focused policies results in neglect of landscape architectural features in transportation infrastructure development, and (3) localized approaches and integrated planning of development relating to transportation lead to greater appreciation and efficiency. From the data gathered, four future development scenarios materialized and were assessed through TOD principles. Zoning and intervention proposals, simulation tests, and a model site for a mixed-use development type were created, promoting public transportation landscapes centered on the needs of pedestrians and commuters.
Include appendices
Thesis (Bachelor of Landscape Architecture) -- University of the Philippines Diliman
Keywords: Landscapes -- Planning; Transportation -- Guiguinto (Bulacan); transit-oriented development -- Guiguinto (Bulacan)